About Some Ethnopolitical and Economical Aspects in the Process of State-Building of Kazakhstan and Kyrgyzstan - NURDINOVA, Zhanetta T.; KOLESNIKOV, Yuriy A.; KISELEVA, Alla V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).32, 2019)
The urgency of the issue researched is stipulated by the fact that in current conditions ethnic identity is not always dominant, much greater importance is given to the level of education and training of every individual, their communication skills etc. Meanwhile, belonging to the people’s culture, the ability to share common values and norms remain still relevant, both for the harmonization of the inner world of the personality as well as in general for the possibilities of social realization. The article highlights some ethnopolitical aspects in the process of state-building of Kazakhstan and Kyrgyzstan. The positions prevailing in the Russian, Kazakhstan, Kyrgyzstan and foreign scientific thought on the specified range of problems have been analyzed. The purpose of the article is to analyze the ethno-political processes influencing the formation of the statehood of Kazakhstan and Kyrgyzstan. In the work, complex scientific and methodological tools have been used: historical, sociological, political, institutional, comparative, system and structural-functional methods of cognition. The materials of the article suggest practical significance for university professors of sociological and legal specialties.